Fodder Yield and Quality of Sugargraze, Sorghum and Maize as Affected by Nitrogen Sources - Kar, Suraj; Singh, Magan; Kumar, Rakesh; Kumar, Parveen (Indian Journal of Animal Nutrition, 2018)
A field experiment was conducted during kharif season of the year 2014 at Forage Research and Management Center, ICAR-National Dairy Research Institute, Karnal, Haryana to compare the effect of different sources of fertilizers on quality aspects of sugargraze, sorghum and maize crops. The results showed that DM content was the highest in sorghum (23.83%) while, CP content (10.42 %), EE content (1.66%) andnutrient yields were highest in sugargraze. However, ash (17.10%) and NDF contents (62.27%) were the highest in sorghum. The hemicellulose level was the maximum in maize (25.15%). Among different sources of fertilizers, 100% nitrogen through inorganic sources was better in comparison to other sources irrespective of crops under study.